2013
DOI: 10.7883/yoken.66.512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Test Methods for Detecting Metallo-β-Lactamase-Producing Gram-Negative Bacteria

Abstract: SUMMARY:The recent increase in gram-negative bacteria coproducing multiple classes of blactamases has made it difficult to accurately identify metallo-b-lactamase (MBL) producers. In the present study, six methods for detecting MBL producers were compared using 56 gram-negative bacterial isolates that produce various b-lactamases. Sodium mercaptoacetic acid (SMA) and EDTA were used as inhibitors for a double-disk synergy test (DDST), and antimicrobial agents, including ceftazidime (CAZ), imipenem, and meropene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…They were selected by ChromID ESBL and confirmed by a double-disk synergy test (DDST) using inhibitor (4,5). E. coli TK1044 and K. pneumoniae TK1238 were isolated from a traveler from Bangladesh in January 2013 and a traveler returning from Indonesia in February 2014, respectively.…”
mentioning
confidence: 99%
“…They were selected by ChromID ESBL and confirmed by a double-disk synergy test (DDST) using inhibitor (4,5). E. coli TK1044 and K. pneumoniae TK1238 were isolated from a traveler from Bangladesh in January 2013 and a traveler returning from Indonesia in February 2014, respectively.…”
mentioning
confidence: 99%
“…On the basis of these results, we conclude that the SMA test using both the MPM and CAZ disks is the most suitable method for screening carbapenemresistant isolates for NDM-1-type MBL producers. As reported previously (8), this combination also allows for highly sensitive and specific detection of the IMP-and VIM-type MBL producers. Effective screening of MBL producers, including the NDM-1 type and other MBL types, can therefore be performed by the SMA test using MPM and CAZ disks in clinical laboratories followed by confirmation of the MBL genes by PCR analysis in specialized laboratories.…”
mentioning
confidence: 52%
“…This test uses a Kirby-Bauer (KB) disk containing a b-lactam antibiotic (ceftazidime [CAZ] recommended) and a disk containing SMA, an MBL inhibitor that can bind to the MBL active site through interactions with zinc ions (6). Although this test works well for the detection of IMPand VIM-type MBL producers, which are the predominant MBL types in Japan (7), preliminary results have indicated that it may fail to detect NDM-1 producers when using the SMA test with the CAZ disk according to general recommendations (8). Hence, the present study aimed at improving the SMA test by replacing the CAZ disk for detecting NDM-1 producers among Enterobacteriaceae and Acinetobacter baumannii.…”
mentioning
confidence: 99%
“…CPE isolates often coproduce various classes of β-lactamases, such as ESBL and CMY-type β-lactamases, and such coproduction has increasingly hampered the accurate identification of β-lactamases produced in clinical isolates in routine microbiology testing (Birgy et al, 2012;Hattori et al, 2013;Pitout and Laupland, 2008;Poulou et al, 2014). To address this problem, we generated a novel chromogenic method, the Pentawell test, which enables the prompt identification and classification of β-lactamases coproduced in clinical Enterobacteriaceae isolates.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypic methods are simple and inexpensive but are often not effective in discriminating clinical isolates producing plural classes of β-lactamases because of the masking effect conferred by the additional production of other classes of β-lactamases (Birgy et al, 2012;Hattori et al, 2013;Pitout and Laupland, 2008;Poulou et al, 2014). Therefore, we developed a novel method, the Penta-well test, which enables the identification of plural classes of β-lactamases in a single batch test.…”
Section: Introductionmentioning
confidence: 99%